Binding energies and radii of α-cluster-type nuclei from calculations based on the strictly restricted dynamics model - Krasta, T.; Ruža, J.; Tambergs, J.; Katkevičius, O.; Castilho Alcarás, J. A. [UNESP] (Pleiades Publishing, 2002)
The properties of α-cluster-type nuclei with 4 ≤ A ≤ 80 are studied by employing the microscopic strictly restricted dynamics model (SRDM). The SRDM parameter set found via a fit to the experimental and theoretical values of nuclear binding and excited-level energies, classified according to the ground-state SU3 configurations, includes a nuclear-radius parameter r0 entering into the expression R = r0A1/3 [fm], as well as the parameters of the effective central N N-interaction potential. The use of the microscopic SRDM allows one to obtain additional information about nuclei along the Z = N line, including binding energies, radii, and spectra of low-lying levels. The calculated nuclear binding energies and nuclear root-mean-square radii 〈r2〉1/2 are in reasonable agreement with their experimental counterparts. © 2002 MAIK Nauka/Interperiodica.